Application of tilt sensor in headset operator surveilance camera control system for people with disabilities - Anita Ahmad 486221; Universiti Teknologi Malaysia. Fakulti Kejuruteraan Elektrik; Universiti Teknologi Malaysia. Pusat Pengurusan Penyelidikan 520 (Skudai : Universiti Teknologi Malaysia, 2006)
PSZJBL